A performance study of the wavelet-phase stability (WPS) in auditory selective attention - Low , Yin Fen (Elsevier Inc., 2011)
Large-scale neural correlates of auditory selective attention reflected in the electroencephalogram (EEG) have been identified by using the complex wavelet-phase stability measure (WPS). In this paper, we study the feasibility of using this amplitude independent measure, the WPS in extracting the correlates of attention by comparing its performance to the widely used linear interdependency measures, i.e., the wavelet coherence and the correlation coefficient. The outcome reveals that the WPS outperforms the other two measures in discriminating both the attended and unattended single sweep auditory late responses (ALRs). It is concluded that the proposed WPS provides a faster (in terms of less sweeps which are required) and robust objective quantification of selective attention.